Dyscalculia in Higher Education Systems, support and student strategies - Clare Trott (2015)
In the UK in 2010 The Equality Act came into force. This carries forward the foundations laid down by previous legislation (The Special Educational Needs and Disability Act (SENDA) 2001, and The Disability Discrimination Act (DDA) 1995). According to the legislation, there is a requirement for institutions to make ‘reasonable adjustments’ for disabled students to facilitate access to goods and services. As well as this, institutions are required to ensure disabled students do not receive less favourable treatment nor are unfairly disadvantaged due to a reason associated with their disability. Institutions are further entrusted to put in place ‘anticipatory measures’. This might include materials produced in an appropriate and accessible format, provision of note-takers or alternative examination and assessment arrangements for students where required. The duty is to make reasonable adjustments anticipatory. In terms of dyscalculia, Higher Education Institutions (HEIs) must consider the reasonable adjustments they may need to put in place in order to ensure the removal of unnecessary barriers in respect of the mathematical aspects of courses. HEIs must also promote best practice for inclusion at all levels.